2021
DOI: 10.21203/rs.3.rs-240084/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Looking for Consistency in an Uncertain World: Test-Retest Reliability of Neurophysiological and Behavioral Readouts in Autism

Abstract: BackgroundAutism spectrum disorders (ASD) are associated with altered sensory processing and perception. Scalp recordings of electrical brain activity time-locked to sensory events (event-related potentials; ERPs) provide precise information on the time-course of related altered neural activity, and can be used to model the cortical loci of the underlying neural networks. Establishing the test-retest reliability of these sensory brain responses in ASD is critical to their use as biomarkers of neural dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Thus, although emerging evidence highlights possible differences in neural mechanisms of biological motion processing in ASD, as well as potential implications for social function, a high degree of inconsistency in ndings makes it di cult to draw de nitive conclusions. Variability in ndings cannot be accounted for by within-subject unreliability as several studies have shown that behavioral and electrophysiologic responses to visual paradigms are highly consistent within individuals on repeated measures (45,46). Instead, potential mediators of such study heterogeneity may include betweensubjects developmental, cognitive and/or attentional factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although emerging evidence highlights possible differences in neural mechanisms of biological motion processing in ASD, as well as potential implications for social function, a high degree of inconsistency in ndings makes it di cult to draw de nitive conclusions. Variability in ndings cannot be accounted for by within-subject unreliability as several studies have shown that behavioral and electrophysiologic responses to visual paradigms are highly consistent within individuals on repeated measures (45,46). Instead, potential mediators of such study heterogeneity may include betweensubjects developmental, cognitive and/or attentional factors.…”
Section: Introductionmentioning
confidence: 99%